Disentangling temporal food web dynamics facilitates understanding of ecosystem functioning. Issue 5 (9th March 2021) - Kortsch, Susanne; Frelat, Romain; Pecuchet, Laurene; Olivier, Pierre; Putnis, Ivars; Bonsdorff, Erik; Ojaveer, Henn; Jurgensone, Iveta; Strāķe, Solvita; Rubene, Gunta; Krūze, Ēriks; Nordström, Marie C.
Abstract: Studying how food web structure and function vary through time represents an opportunity to better comprehend and anticipate ecosystem changes. Yet, temporal studies of highly resolved food web structure are scarce. With few exceptions, most temporal food web studies are either too simplified, preventing a detailed assessment of structural properties or binary, missing the temporal dynamics of energy fluxes among species. Using long‐term, multi‐trophic biomass data coupled with highly resolved information on species feeding relationships, we analysed food web dynamics in the Gulf of Riga (Baltic Sea) over more than three decades (1981–2014). We combined unweighted (topology‐based) and weighted (biomass‐ and flux‐based) food web approaches, first, to unravel how distinct descriptors can highlight differences (or similarities) in food web dynamics through time, and second, to compare temporal dynamics of food web structure and function. We find that food web descriptors vary substantially and distinctively through time, likely reflecting different underlying ecosystem processes. While node‐ and link‐weighted metrics reflect changes related to alterations in species dominance and fluxes, unweighted metrics are more sensitive to changes in species and link richness. Comparing unweighted, topology‐based metrics and flux‐based functions further indicates that temporal changes in functions cannot be predicted using unweighted food web structure. Rather, information on species population dynamics and weighted, flux‐based networks should be included to better comprehend temporal food web dynamics. By integrating unweighted, node‐ and link‐weighted metrics, we here demonstrate how different approaches can be used to compare food web structure and function, and identify complementary patterns of change in temporal food web dynamics, which enables a more complete understanding of the ecological processes at play in ecosystems undergoing change. Abstract : This study shows how unweighted and weighted food web network descriptors vary substantially and distinctively through time (1981–2014). The full extent of the temporal food web changes reported was only revealed through the complementarity between unweighted and weighted network approaches linking structure and function.